Immunogenicity of pneumococcal vaccines in comorbid autoimmune and chronic respiratory diseases - Koji Kuronuma; Hiroki Takahashi (Taylor & Francis Group, 2019)
Streptococcus pneumoniae causes pneumonia, meningitis, otitis media, and bacteremia. The mortality and morbidity of invasive pneumococcal disease are high among adults aged >65 years or those with underlying chronic or immunosuppressive conditions. A recent systematic review showed that patients treated with immunosuppressive agents have impaired immune responses to pneumococcal conjugate vaccine (PCV) and pneumococcal polysaccharide vaccine compared with healthy subjects. A more favorable response is observed in patients treated with tumor necrosis factor-alpha-blocking agents compared with those treated with other immunosuppressive agents. Low systemic corticosteroid doses do not affect the responses to pneumococcal vaccines. Patients with human immunodeficiency virus and idiopathic pulmonary fibrosis receiving immunosuppressive therapy exhibit decreased immunogenicity to pneumococcal vaccines. The effects of T-cell-dependent PCV possibly depend on host memory B cells in some disease conditions. Several immunosuppressive therapy types and disease conditions may affect the responses to pneumococcal vaccines. Immunization should be administered before immunosuppressive medication initiation whenever possible.